Affect and the role of client sophistication on satisfaction judgments within business-to-business professional services - Garry, Anthony Joseph (2008)
Evidence which demonstrates a link between the affective dimension and satisfaction in a tangible product based context is well documented. However, when placed in a credence service context the role of Affect becomes more complex insofar as research suggests that consumers will partly use their affective reaction to the service provider when evaluating overall satisfaction. However, previous research in this field has assumed consumer homogeneity when there is increasing evidence of consumer heterogeneity. Consequently, this research attempts to address this deficiency by exploring the role of Affect evoked among consumers of differing sophistication within the business-to-business credence service context of corporate legal services. To this end, a three-stage methodology is adopted incorporating explorative interviews, experimentally generated scenarios and a survey comprising of 252 users of corporate legal services within the UK.